Assessing Musical Abilities Objectively: Construction and Validation of the Profile of Music Perception Skills - Law, Lily N. C.; Zentner, Marcel (PLOS ONE, 2012)
A common approach for determining musical competence is to rely on information about individuals’ extent of musical training, but relying on musicianship status fails to identify musically untrained individuals with musical skill, as well as those who, despite extensive musical training, may not be as skilled. To counteract this limitation, we developed a new test battery (Profile of Music Perception Skills; PROMS) that measures perceptual musical skills across multiple domains: tonal (melody, pitch), qualitative (timbre, tuning), temporal (rhythm, rhythm-to-melody, accent, tempo), and dynamic (loudness). The PROMS has satisfactory psychometric properties for the composite score (internal consistency and test-retest r>.85) and fair to good coefficients for the individual subtests (.56 to.85). Convergent validity was established with the relevant dimensions of Gordon’s Advanced Measures of Music Audiation and Musical Aptitude Profile (melody, rhythm, tempo), the Musical Ear Test (rhythm), and sample instrumental sounds (timbre). Criterion validity was evidenced by consistently sizeable and significant relationships between test performance and external musical proficiency indicators in all three studies (.38 to.62, p<.05 to p<.01). An absence of correlations between test scores and a nonmusical auditory discrimination task supports the battery’s discriminant validity (−.05, ns). The interrelationships among the various subtests could be accounted for by two higher order factors, sequential and sensory music processing. A brief version of the full PROMS is introduced as a time-efficient approximation of the full version of the battery.